Probing Prompting Improves Junior High School Students' Mathematical Reasoning During the Implementation of Community Activities Restrictions - Harisuddin, Muhammad Iqbal (FKIP Universitas Lampung, 2023)
Abstract: This research aims to determine the effect of using the probing-prompting technique in significantly improving students' mathematical reasoning abilities in class and to determine students' responses to the application of the probing-prompting technique in mathematics learning during the implementation of restrictions on community activities (PPKM). In this research, quasi-experimental research was used, a Nonequivalent Control Group Design research design. The research was conducted in the odd semester of the 2021-2022 academic year with a population of all class VIII students. The experimental class that received mathematics learning using the Probing Prompting learning model experienced a significant increase with a positive response in mathematics learning during the implementation of restrictions on community activities (PPKM) with a value of 0.70 in the high improvement category. Meanwhile, the control class with the usual learning model experienced an increase of 0.41 with a moderate increase. Keywords: ordinary learning, ppkm, probing prompting, reasoning Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan teknik probing-prompting dalam peningkatan kemampuan penalaran matematis siswa dikelas secara signifikan dan untuk mengetahui respon siswa terhadap penerapan teknik probing-prompting dalam pembelajaran matematika pada masa pemberlakuan pembatasan kegiatan masyarakat (PPKM). Dalam penelitian ini digunakan penelitian kuasi eksperimen, desain penelitian Nonequivalent Control Group Design. Penelitian dilakukan pada semester ganjil tahun ajaran 2021-2022 dengan populasi dalam seluruh siswa kelas VIII. Kelas eksperimen yang mendapat pembelajaran matematika dengan menggunakan model pembelajaran Probing Prompting mengalami peningkatan signifikan dengan respon yang positif dalam pembelajaran matematika pada masa pemberlakuan pembatasan kegiatan masyarakat (PPKM) dengan nilai sebesar 0,70 kategori peningkatan tinggi. Sedangkan kelas kontrol dengan model pembelajaran biasa mengalami peningkatan sebesar 0,41 dengan peningkatan sedang. Kata kunci: pembelajaran biasa, penalaran, ppkm, probing prompting DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp810-824